2022
DOI: 10.3389/fnut.2022.851980
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin A Status Is More Commonly Associated With Symptoms and Neurodevelopment in Boys With Autism Spectrum Disorders—A Multicenter Study in China

Abstract: BackgroundAutism spectrum disorder (ASD) is a neurodevelopmental disorder, and show a striking male bias in prevalence. Vitamin A (VA) is essential for brain development, and abnormalities in its metabolite retinoic acid are associated with the pathophysiology of ASD. This national multicenter study was conducted to investigate the relationship between serum VA level and core symptoms in ASD children and whether there are still sex differences.MethodA total of 1,300 children with ASD and 1,252 typically-develo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…GSEA suggested that propofol-induced neurotoxicity was associated with processes such as activation of CD8 + T cells, B cell maturation and transcription of Pam3CSK4. Enrichment analysis showed that propofol-induced neurotoxicity involved processes such as activation of immune cells and JAK/STAT and MAPK signaling pathways, nervous system development, vascular regeneration, and oxidative stress [19][20][21][22][23].…”
Section: Discussionmentioning
confidence: 99%
“…GSEA suggested that propofol-induced neurotoxicity was associated with processes such as activation of CD8 + T cells, B cell maturation and transcription of Pam3CSK4. Enrichment analysis showed that propofol-induced neurotoxicity involved processes such as activation of immune cells and JAK/STAT and MAPK signaling pathways, nervous system development, vascular regeneration, and oxidative stress [19][20][21][22][23].…”
Section: Discussionmentioning
confidence: 99%
“…In China, ∼0.7 % of children aged 6–12 years suffer from ASD [16] . Patients with ASD in China have an overall lower VA level than typical controls, especially in boys with ASD [17] , [18] , [19] , [20] , [21] , [22] , [23] . Negative correlations between serum VA concentration in patients with ASD and the corresponding symptom severity were identified using the Childhood Autism Rating Scale, Autism Behaviour Checklist, and Social Responsiveness Scale [19] , [21] , [24] .…”
Section: Introductionmentioning
confidence: 97%
“…The prevalence of autism is notably higher in boys, exceeding four times that in girls. Additionally, individuals with autism frequently experience co-occurring conditions, including epilepsy, depression, anxiety, and attention deficit hyperactivity disorder, along with challenging behaviors like sleep disturbances and self-harm [11] The onset of autism is influenced by a combination of genetic factors and early environmental exposures during development [12][13]. Genetic variations in certain genes significantly elevate the risk of ASD.…”
Section: Introductionmentioning
confidence: 99%